Existence of Positive Solutions for p-Laplacian Dynamic Equations with Derivative on Time Scales - Jinjun Fan; Liqing Li (Journal of Applied Mathematics)
We consider the existence of positive solutions of nonlinear p-Laplacian dynamic equations with derivative on time scales. Applying the Avery-Peterson fixed point theorem, we obtain at least three positive solutions to the problem. An example is also presented to illustrate the applications of the obtained results.